2017
DOI: 10.1126/sciadv.1602231
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional positioning and structure of chromosomes in a human prophase nucleus

Abstract: High-resolution three-dimensional structure of chromosomes in a human prophase nucleus from electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 32 publications
(40 reference statements)
0
40
0
Order By: Relevance
“…Studies that have mapped intranuclear locations of chromosomal regions by FISH (Boyle et al, 2001; Cremer et al, 2003; Cremer et al, 2001), chromosome conformation capture (Di Stefano et al, 2016; Kalhor et al, 2012), or block-face scanning electron microscopy (Chen et al, 2017) have concluded that areas relatively enriched in genes preferentially partition to the interior region of the nucleus, while gene-sparse regions tend to associate with the periphery. As it is well established that HIV-1 integration overwhelmingly targets gene rich chromosomal regions (Koh et al, 2013; Ocwieja et al, 2011; Schaller et al, 2011; Schroder et al, 2002; Sowd et al, 2016) (Figure S5), such observations are inconsistent with the nuclear periphery playing a major role in determining integration site selection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have mapped intranuclear locations of chromosomal regions by FISH (Boyle et al, 2001; Cremer et al, 2003; Cremer et al, 2001), chromosome conformation capture (Di Stefano et al, 2016; Kalhor et al, 2012), or block-face scanning electron microscopy (Chen et al, 2017) have concluded that areas relatively enriched in genes preferentially partition to the interior region of the nucleus, while gene-sparse regions tend to associate with the periphery. As it is well established that HIV-1 integration overwhelmingly targets gene rich chromosomal regions (Koh et al, 2013; Ocwieja et al, 2011; Schaller et al, 2011; Schroder et al, 2002; Sowd et al, 2016) (Figure S5), such observations are inconsistent with the nuclear periphery playing a major role in determining integration site selection.…”
Section: Discussionmentioning
confidence: 99%
“…Serial block‐face scanning electron microscopy (SBFSEM) is a method to generate high resolution 3D images from small samples, [ 116 ] which is benefit to directly observe interfacial microstructure in ASSBs. For example, Huang et al introduced g‐C 3 N 4 as a new interface enabler into Li metal to transit the Li metal/garnet‐type SSE interface from point contact to intimate contact and hence to improve the electrochemical performance especially to suppress the Li dendrite formation.…”
Section: Characterization Techniques For Interface In All‐solid‐statementioning
confidence: 99%
“…The knife can also quickly remove a greater volume of material than the ion beam of the FIBSEM, meaning that larger volumes of tissue can feasibly be scanned (figure 3). Both techniques can reach a minimum X,Y pixel size of around 3-5nm (Daum et al, 2017;Feeney et al, 2018) however voxel size in the Zdirection is at best 20nm in SBFSEM (Chen et al, 2017) (a limit set by the cutting of the knife) whereas FIBSEM allows the milling of arbitrarily thin sections. Compared to ssTEM, both FIBSEM and SBFSEM sacrifice ultimate resolution in exchange for greater ease of use and reliability: both block face techniques allow the user to leave the microscope on 'autopilot' once a run has been initiated (assuming there are no problems encountered with cutting/milling or imaging), and thus the total work hours needed to produce a complete dataset are vastly reduced.…”
Section: Serial Block Face Scanning Electron Microscopymentioning
confidence: 99%
“…A recent study examined the morphology of carnivorous plant nuclei in order to examine novel membrane extensions (Plachno et al, 2017). Sub-nuclear structures such as individual chromosomes (Chen et al, 2017) and the mitotic spindle (Nixon et al, 2017) have been imaged and modelled. At the nanometer scale, SBFSEM is able to resolve structures such as vesicles (Chuang et al, 2015), T-tubules (Pinali et al, 2013) and the cristae of mitochondria (Vincent et al, 2016).…”
Section: Serial Block Face Scanning Electron Microscopymentioning
confidence: 99%